Transformation and Revitalization of Human Resources at Citra Negara Vocational School - Agustin Wijayanti; Rohmat TZ; Henny Suharyati (Dinasti International Journal of Education Management And Social Science, 2025)
The COVID-19 pandemic has triggered a major transformation in education, especially in SMK Citra Negara which focuses on vocational education. This study aims to evaluate the resistance of generation Z teachers to the implementation of technology-based educational transformation and industry needs. Using a qualitative approach, data were collected through interviews, observations, and document analysis. The results of the study indicate that although technology-based curriculum is able to bridge the gap between education and the world of work, resistance among generation Z teachers remains a challenge. Causal factors include lack of training, administrative burden, and limited access to technology. Strategies such as needs-based training, mentoring, and collaboration with industry partners have proven effective in reducing resistance. This study concludes that strong institutional support and a collaborative approach are key to the success of vocational education transformation.